1988
DOI: 10.1007/bf02470843
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphnode dissection procedure during esophageal cancer operation—Carefully considered for preserving respiratory function

Abstract: In 22 patients with esophageal cancer, mediastinal lymphnode dissection procedure, with preservation of the right bronchial artery and pulmonary branches of the right vagus nerve, was performed during radical esophagectomy. In patients who underwent this procedure, respiratory function was sufficiently maintained against severe complications and the operative and hospital death rate was less than that of other esophagectomized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…This may result from the fact that the anterolateral thoracotomy performed in our present surgical procedure, with an incisional length of 13-15 cm, can preserve the serratus anterior muscle and the latissimus dorsi muscle. In addition, the bronchial artery and the bronchial branches of the vagus nerve are usually preserved in the upper mediastinal lymphadenectomy, resulting in preservation of the physiological tolerance to surgical stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…This may result from the fact that the anterolateral thoracotomy performed in our present surgical procedure, with an incisional length of 13-15 cm, can preserve the serratus anterior muscle and the latissimus dorsi muscle. In addition, the bronchial artery and the bronchial branches of the vagus nerve are usually preserved in the upper mediastinal lymphadenectomy, resulting in preservation of the physiological tolerance to surgical stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…Protective measures include preservation of the bronchial arteries during resection in addition to careful dissection around the airway. 41 For the salvage esophagectomy procedure, the right posterior bronchial artery should be preserved, and neck dissection should be avoided to preserve the blood supply from the inferior thyroidal artery to the trachea.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…An experimental study using dogs suggested that bilateral thoracotomy itself did not always cuase more critical respiratory insuf ficiency as compared with right thoracotomy [17], The conception that the insurance of satisfactory surgical view is the most important factor in the safe and complete removal of the regional lymph nodes led us to choose the approach through a left oblique thoracolaparotomy and a right posterolateral thoracotomy. Some recent advances in operative technique, such as careful preservation of the right bronchial artery and pulmonary branches of the right vagus nerve, decreased the incidence of severe respi ratory complications [3,4], We also preserved the right bronchial artery to preserve the regional blood flow of the trachea and the main bronchus, and preserved the pulmo nary branches of the right vagus nerve to maintain suffi cient excretion of sputum. In the present study, extubation of a tracheal tube was possible within 3 days after operation in all patients and there was no postoperative respiratory complication in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…Radical operation for thoracic esophageal cancer, in cluding aggressive mediastinal lymph node dissection, is usually performed through a right posterolateral thoracot omy, a laparotomy and a cervical approach [1][2][3]. For bet ter exposure of the whole posterior mediastinum, a right posterolateral thoracotomy should be chosen [5,6].…”
Section: Introductionmentioning
confidence: 99%